The Role Of Tax Volunteers (Renjani) As Social Media Influencers (SMI) On The Perceptions Of Individual Taxpayers - Angelica Yohana Santika Lemmuela; Servatia Mayang Setyowati (UNIVED Press, 2026)
This study aims to analyze the role of Relawan Pajak untuk Negeri (Renjani) as social media influencers (SMI) in raising tax awareness among individual taxpayers (WPOP). Using a qualitative approach and interviews with 10 WPOP, 8 Renjani members, and 1 representative from the Directorate General of Taxes (DJP), this study explores how the educational content shared by Renjani on social media influences taxpayers' perceptions and intentions. The credibility theory serves as the primary foundation, focusing on three dimensions: attractiveness, trustworthiness, and expertise. The findings indicate that Renjani is perceived as credible in conveying tax information in an engaging, relevant, and easily understandable manner. The informal and contextual communication style is deemed more effective in reaching the younger generation compared to the formal approach of tax authorities. These findings indicate that Renjani plays a strategic role in building tax awareness, bridging communication between the DGT and the digital community, and strengthening tax inclusion in the social media era. This study recommends optimizing digital communication strategies and strengthening training for Renjani to enhance the impact of tax education in the future.